2021
DOI: 10.3390/ijms22115808
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Diabetic Kidney Disease: Focus on Hormonal, Genetic and Clinical Factors

Abstract: Diabetic kidney disease (DKD) is one of the most serious complications of both type 1 (T1DM) and type 2 diabetes mellitus (T2DM). Current guidelines recommend a personalized approach in order to reduce the burden of DM and its complications. Recognizing sex and gender- differences in medicine is considered one of the first steps toward personalized medicine, but the gender issue in DM has been scarcely explored so far. Gender differences have been reported in the incidence and the prevalence of DKD, in its phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
1
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 239 publications
(288 reference statements)
1
46
1
13
Order By: Relevance
“…Parker et al [ 63 ], in their meta-analysis, examined the link between 25(OH) vitamin D levels and cardiometabolic disorders: a higher level of this hormone was linked to a 43% reduction in cardiometabolic dysregulation. The results of the study demonstrated that higher levels of vitamin D were associated with a considerable reduction of CVD, type 2 diabetes, and metabolic syndrome [ 64 ]. However, these considerations are speculative, the current literature presents methodological limitations, and it is still uncertain whether vitamin D low levels can have a predictive role in CVD and CRS outcomes.…”
Section: Biomarkers Connecting the Heart And Kidneymentioning
confidence: 99%
“…Parker et al [ 63 ], in their meta-analysis, examined the link between 25(OH) vitamin D levels and cardiometabolic disorders: a higher level of this hormone was linked to a 43% reduction in cardiometabolic dysregulation. The results of the study demonstrated that higher levels of vitamin D were associated with a considerable reduction of CVD, type 2 diabetes, and metabolic syndrome [ 64 ]. However, these considerations are speculative, the current literature presents methodological limitations, and it is still uncertain whether vitamin D low levels can have a predictive role in CVD and CRS outcomes.…”
Section: Biomarkers Connecting the Heart And Kidneymentioning
confidence: 99%
“…The risk of developing DKD has a polygenetic component [20][21][22]. Diabetic patients with a first-degree relative with DKD have a substantially greater risk of developing DKD compared with those who do not have an affected relative [23].…”
Section: Duration Socioeconomic Factors and Familial And Genetic Factorsmentioning
confidence: 99%
“…Chronic kidney disease (CKD) is a serious complication of type 2 diabetes (T2D) that afflicts between 25 and 40% of all diagnosed patients [ 1 ]. CKD progression differs by factors such as age [ 2 ], gender, and genetic [ 3 ] characteristics and entails compromised kidney function or kidney injury attributed to persistent uncontrolled hyperglycemia, the presence and/or release of pro-inflammatory proteins and pro-fibrotic proteins, and hypertension or high intra-glomerular pressure associated with elevated rates of cardiovascular disease (CVD) compared to T2D alone [ 4 ]. This elevated cardiovascular (CV) risk is partially responsible for the heightened mortality risk among patients with CKD, which is markedly higher compared to the general population or patients with T2D alone [ 5 ].…”
Section: Introductionmentioning
confidence: 99%